Categorias sociais e econômicas: o processo de cooperação em três estágios das redes interorganizacionais - Bertóli, Nilson César (2018)
The aim of this thesis is to analyze the process of horizontal interorganizational networks cooperation in three stages. The guiding proposition is to verify the influence of two social categories (trust and commitment) and two economic ones (performance and benefits) in three stages of the networks (birth / formation; growth / development; maturity / success). The research presents data from five interorganizational networks of the region of Londrina-PR, chosen for being organized as concentrations of small and medium-sized enterprises with economic and social importance in the region. Previous signs collected by the author showed movements of rapprochement between entrepreneurs, with formal groups, associations and business cooperatives, which is an opportunity to follow the networks' cooperation configurations. The work is justified from the principle of the social-technical and rational-economic paradigm, uses the basic affirmation of the social-technical paradigm on the presence of social relations as influential categories in the organization of networks (Granovetter, 2007; Bertóli, Giglio and Rimoli, 2015), and the affirmation of the rational-economic paradigm as an influential category, mainly in the period of formation of networks (Vasudeva, Zaheer and Hernandez, 2013, Klein and Pereira, 2014, De Souza et al. , 2015). Thus, it is hoped to contribute to the understanding of the interfaces between social and economic categories as a configuration of interorganizational networks. The present research was characterized by being qualitative, exploratory and multiple cases. An instrument was created - script for semi-structured interviews with open questions. The primary and secondary data supported the proposals of the analytical models for the presentation of the states of the networks in the three stages, leaving no room for doubt, since they indicated the exhaustion by the convergence. As a result, when doing a comparative analysis of the proposed theories in the analytical model and in the conceptual bases with the result found in the five networks investigated. It can be affirmed that the theories used in this study, supported the discussions of each construct analyzed in this thesis. The benefit of this work was to contribute in a theoretical way to the studies in interorganizational networks, in the investigation of the process of cooperation in three stages, using as an interface the influence of the four constructs, and to contribute in a methodological way to the improvement of instruments of collection of qualitative studies in the field of networks. From the managerial perspective, it is expected that the institutions and entrepreneurs of these businesses can use the information for reflection and decision making.